Risk factors for type 2 diabetes mellitus in patients with gout: results from a prospective study - O. V. Zhelyabina; M. S. Eliseev; S. I. Glukhova; M. N. Chikina; T. S. Panevin (Современная ревматология, 2022)
The development of type 2 diabetes mellitus (DM) (DM2) in patients with gout can be influenced by both conventional and directly linked to gout risk factors (RFs).Objective: to identify RFs for the development of DM2 in patients with gout, including those directly associated with gout, based on long-term prospective follow-up data.Patients and methods. The study included 444 patients with gout older than 18 years (49 women, 395 men) who did not have DM. The followup period ranged from 2 to 8 years. The studied RFs for DM2 were: gender, age, family history of DM2, obesity, alcohol consumption >20 units per week, insufficient physical activity, unbalanced nutrition, history of hyperglycemia, coronary heart disease (CHD), arterial hypertension (AH), chronic heart failure, antihypertensive drugs, diuretics, glucocorticoids (GCs), urate-lowering therapy, serum levels of cholesterol, triglycerides, CRP, uric acid (UA), glucose, creatinine, glomerular filtration rate <60 ml/min/1.73 m2, the presence of tophi, >4 attacks of gout per year, ≥5 affected joints during the disease.Results and discussion. DM2 developed in 108 (24.3%) patients. These patients were older, had a family history of DM, more often received antihypertensive therapy, diuretics, and glucocorticoids (49.1; 73.1; 27.8 and 47.2%, respectively) than patients who did not develop DM2 (25.6; 50.5; 14.8 and 36.4%, respectively; p<0.05 for all cases). In addition, patients with DM2 were more likely to have subcutaneous tophi (59.3% versus 30.0%; p=0.001), among them there were more individuals (67.6% versus 31.6%; p=0.001) with frequent attacks of arthritis (>4 attacks per year). UA levels >480 and 600 μmol/l were also significantly more frequent (p=0.0002) in patients with DM2 (71.3 and 34.3%, respectively).According to logistic regression data, factors that increase the risk of developing DM2 were: family history of DM, a history of hyperglycemia, CHD, AH, intake of GCs, antihypertensive drugs, the presence of tophi, >4 exacerbations of gout per year. Febuxostat use and UA <300 μmol/L were associated with a lower risk of DM2.Conclusion. The occurrence of DM2 in gout is associated not only with well-known risk factors, but also with hyperuricemia and microcrystalline inflammation. Febuxostat therapy is associated with a lower risk of developing DM2.